Efficacy of Continuous High Dose Midazolam Infusion in Childhood Refractory Generalized Convulsive Status Epilepticus - Fayyazi, Afshin; Karimzadeh, Parvaneh (Iranian Journal of Child Neurology, 2011)
Objecive Prolonged and uncontrolled refractory status epilepticus (SE) is a life-threatening medical emergency in children (1,2,3). There is no consensus on the optimal therapy for refractory status epilepticus (1). The aim of this study was to develop a new method for treating patients with refractory status epilepticus. Materials & Methods Ten children with refractory status epilepticus in Mofid Hospital, who did not respond to 10 μg/kg per min of intravenous midazolam, had their dose of midazolam increased to 30 μg/kg per min. All children were monitored for the development of side effects. Results Ten children with no response to low-dose midazolam were given a higher dose of midazolam, and 5 (50%) children had a good response. These patients had significantly different response to high-dose midazolam. One patient in the high-dose midazolam group was intubated and required mechanical ventilation. The duration of stay in the hospital and PICU and on mechanical ventilation in patients with no response to low-dose midazolam following with other drugs was longer than in the high-dose midazolam group. No death occurred in high dose midazolam group. Conclusion High-midazolam dose drip infusion is a safe and effective protocol for refractory status epilepticus in children. Keywords: Refractory status epilepticus; midazolam; mortality; childhood